Differences in segmental speeds as a function of maturation in youth baseball pitchers - Washington, J. K.; Gilmer, G. G.; Barfield, J. W.; Gascon, S. S.; Saper, M. G.; Dugas, J. R.; Andrews, J. R.; Oliver, G. D. (International Journal of Sports Medicine, 2018)
The purpose of this study was to determine how stride length, segmental sequencing of the pelvis, trunk, humerus, and forearm velocities and accelerations, and the timing of these values change as youth mature. Thirteen youth baseball pitchers participated at three consecutive time points: visit 1 (10.7±1.3 years; 151.8±10.7 cm; 45.0±9.65 kg), visit 2 (11.5±1.6 years; 155.5±11.1 cm; 50.4±10.0 kg), and visit 3 (12.4±1.7 years; 161.5±11.7 cm; 56.4±10.8 kg). Participants executed three pitches for a strike to a catcher. The maximum value of stride length and segmental speeds and accelerations was recorded. The point at which these maximum values occurred during the throw was calculated as a percentage from hand separation to maximum internal rotation of the shoulder. Repeated measures ANOVAs and Friedman Tests revealed no statistically significant differences between stride length, segmental speeds and accelerations, and their percentage of the pitch between the three visits. However, there was a significant increase in ball velocity across visits. No significant changes occurred in pitching mechanics between the ages of 10-12. The authors speculate the lack of differences can be accounted for because these ages are prior to any significant pubescent changes. Future research should consider pre- and post- pubescent age groups.